ANALISIS PENGARUH PENDEKATAN PERSONAL TENAGA PENJUAL, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN PELANGGAN - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
In a high level of competitive environment, every business must maintain their customer. This study, therefore, intent to search several variables’ effect which is probably able to rise customer satisfaction.The study used several customer of PT WAHANA KREASINDO UTAMA as sample. Data analyze instrument used by the writer is SPSS 17. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. Summary said that personal approach of salesperson, product quality and price are positively effected to customer satisfaction. Based on the result of the study, managerial implication given to the company is suggestion or input to management of PT WAHANA KREASINDO UTAMA to give more concern at the price, as it is the most dominant factor effected to customer satisfaction.